Tensile Properties of Single Cellulosic Bamboo Fiber (Gigantochloa Scortechinii) Using Response Surface Methodology - Salih, AA; Zulkifli, R; Azhari, CH (Taylor & Francis Inc, 2024)
Gigantochloa scortechinii is one of the most well-known bamboo species in Malaysia because of its advantageous physical, morphological and strength properties. This study presented the effect of alkali treatment conditions of single cellulosic bamboo strips fiber following tensile test and optimized the parameters through response surface methodology based on central composite design. Bamboo strips fiber was treated under various alkali concentrations of 2, 4, 6 and 8 wt.% and soaking times of 1, 3, 6, 12, 18 and 24 h. Results showed that the optimum tensile strength at 4 wt.% alkali concentration and 12 h soaking time was improved by 28% compared with water retting condition. The design-Expert software was used to optimize the tensile properties of single cellulosic bamboo strips fiber. The effect of two independent variables, namely, alkali concentration and soaking time, on the optimized tensile properties of a single cellulosic bamboo strips fiber was investigated. Results showed acceptable R-2 and high R-Adj(2) correlation coefficients for tensile strength, reaching 0.6926 and 0.9575, respectively. The high R-2 and R-Adj(2) correlation coefficients for tensile modulus reached 0.9376 and 0.8931, respectively. Overall results showed that the confirmatory experiments show that the error between predicted and actual values does not exceed 5%. thus, the model can be effectively used to predict tensile properties.